Pelaksanaan pilkada serentak di masa pandemi covid-19 perspektif Qowaid Fiqhiyyah - Nuria, Wafiq Sinta (Maliki Interdisciplinary Journal, 2024)
This study analyzes the implementation of simultaneous Regional Head Elections (Pilkada) during the Covid-19 pandemic from the perspective of qowaid fiqhiyyah. This research method is an analysis approach to Islamic law, using qowaid fiqhiyyah as a basis for analyzing the implementation of simultaneous local elections during a pandemic. Literature study and related research will be used to obtain data. The results of this study are: First, Maqasid al-Shariah (objects of sharia). In the context of simultaneous Pilkada during a pandemic, this perspective helps in determining the most appropriate actions to maintain public safety and health as the main objective. Second, dharurat (emergency). These principles assist in interpreting religious law and provide flexibility in dealing with emergencies or emergencies such as the Covid-19 pandemic. Third, the principle of public interest. In the context of simultaneous Pilkada during a pandemic it is used as a basis for making decisions related to the implementation of elections. Fourth, Hifz al-Aql (protection of the mind). In the context of simultaneous Pilkada during a pandemic, this principle can be used to promote rational action and minimize the risk of spreading the virus. Fifth, human glory and dignity. In this context it teaches that individual rights must be respected and the protection of their health takes precedence.